The influence of sports-related factors on left heart chambers in young female athletes - Damirbek Abibillaev; Aida Baatyrbekova; Fuat Kocyigit; Sergei Petrovsky; Andrey Polubabkin; Aisanam Abdurasulova; Kudaibergen Osmonaliev; Ryskul Kydyralieva; Taalaibek Kudaiberdiev (Heart Vessels and Transplantation, 2024)
Objective: Athletic heart syndrome (AHS) represents a physiological and morphological adaptation of the heart to long-standing intensive training. Left ventricular (LV) chamber sizes are primarily affected by the complex interplay of sports-associated factors. AHS in females substantially varies from males due to underlying physiological, hormonal, and anthropometric differences. This study aims to explore the influence of sports-related factors on left heart chambers in young female athletes (FA).